Monitoreo ambiental del ruido, calidad del aire y agua en la empresa Trimasa. Puerto Bahia. Punchana.Maynas. 2022 - Mauricio Navas, Berny Jean Pierre (2024)
The objective of this work was to analyze the environmental parameters of air, water and noise in the Bahía port where the company TRIMASA is located in the year II[1]2021 and I -2022. Due to its approach, it was quantitative, retrospective, simple descriptive and of a non-experimental design. The sample was defined by the monitoring carried out in the second half of 2021 and the first half of 2022 in the environment of the TRIMASA company in the Bahía port. Punchana, inclusion and exclusion criteria were taken into account, the technique was measurement and the instruments used were the sound level meter, partisol equipment, etc. The data was processed and tabulated with Excel. The results on noise monitoring report results below of the Environmental Quality Standard (ECA) for noise of 80 dB as established in D.S. No. 085-2003-PCM. Regarding air monitoring, results are reported below the ECAs in accordance with the provisions of D.S. N° 003-2017-MINAM, in aspects of sulfur dioxide (SO2), Nitrogen Dioxide (NO2), carbon monoxide (CO), particulate matter (PM10) and (PM2.5) and on water quality, Likewise, results below the RCTs are reported in accordance with the provisions of: D.S. N° 085-2003-PCM in aspects of dissolved oxygen, PH, oils and fats, biochemical oxygen demand, TSS and total petroleum hydrocarbons. These results found lead us not to reject the research hypothesis assumed in the sense that the quality of the environmental parameters of air, water and noise evaluated in the Trimasa company located in the BahÌa port meets the environmental quality standards according to DS No. 004-2017 MINAM.